Work-life balance (WLB) and musculoskeletal discomfort (MSD): a study among female office workforces in Malaysia - Ismail Maakip; Voo, Peter Su Kiong; Azizi Yahaya; Romzi Ationg (Journal of critical reviews, 2020)
Work-life imbalance (WLB) has been linked with ill-health such as burnout, psychological healthiness, and psychological distress. However, less we knew about the latent link between WLB and musculoskeletal discomfort (MSD), particularly in developing countries. This study aim at examining the link between work-life balance and musculoskeletal discomfort in female office workforces in Malaysia. A crosssectional study was employed in which data from female office workers (N=311) completed a survey measuring work-life balance, psychosocial and physical hazards, workload, and MSD levels. The study, found that the musculoskeletal discomfort was significantly associated with physical hazards (β= .39), workload (β= .16) and work-life balance ((β= -.15) [R² =0.23, adjusted R² = 0.22; F (4, 297) = 20.51, p=0.001]. The findings also demonstrated that poor work-life balance is a risk factor associated with MSD. Thus, it is now clear that the MSD is influenced by higher physical demands and workload as well as poor work-life balance experienced by female office workers. Work-life balance is an important risk factor associated with MSD. Given this, work-life balance should be incorporated in the development of workplace policy to minimize MSD and for health promotion at the workplace.